ANALISIS KADAR KLORIDA PADA AIR SUMUR GALI DI BANJAR TELAGA, DESA KUTAMPI KALER, KECAMATAN NUSA PENIDA, KABUPATEN KLUNGKUNG DENGAN TITRASI ARGENTOMETRI - I Wayan Pira Adi Pratama; I Made Oka Adi Parwata; Putu Gede Subhaktiyasa (Stikes Wira Medika Bali, 2017)
Introduction : Water is the main of live for the living things especially human being. The function of water for living can’n be change by another soul. In coatal area is the area that often get difficulties to get clean water access, because often happen of instruction of sea water that cause high of clorida content. In plain water clorida ion at water work can cause corosi vitas on instrument that made from metal and salty taste on the water. The aim of the research to determine degree of clorida ion and analisis of quality of well water that dig by the inhabitant at banjar telaga kutampi village kaler nusa penida district, Klungkung regency. Method : The determining of clorida ion degree do by titrasi argentometri method mohr. Clorida degree from five sample dig well water in mg/L unit in succession: 310,8255, 1.196,5347, 1.716,0163, 560,1336, and 1.185,0225. Result : The things that can polluted well water is that the nearest distance of well with can raised clorida degree in well water. Because well water near with the beach will easy get sea water instruction or leak of sea water to well water. Based on Permenkes Republic of Indonesia number 492/Menkes/Per/IV/2010. The limit of clorida ion maximum 250 mg/L where the sample of degree that can be say the quality of five well water sample is not good from its clorida degree